PENGARUH CEO POWER TERHADAP KINERJA PERUSAHAAN DENGAN PERAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI - Muhammad Noval (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
The purpose of this research is to examine the effect of CEO power onfirm performance and the moderating influence of independent board on therelationship between CEO power and firm performance. Indicator of CEOsPower studied were the CEO ownership in the company (CEO Ownership).The firm performance studied with the calculation of PE Ratio. Then, theindependent board is a proportion of independent board on the board ofcommissioners.The research is conducted by quantitative methods using secondarydata. Secondary data comes from the company's annual report listed on theIndonesian Stock Exchange. This research population is company listed onthe Indonesian Stock Exchange, and then the samples were taken bypurposive sampling with criteria manufacture company that not sufferedlossesduringthe observation process and have the data required in this study,in order to obtaina sample of 267 companies. This study use sregressionanalysis to the test the parameters individually significant (t - test).The result of the hypothesis test indicates that the CEO Powerwith CEO ownership as indicator has no effecton the firm performance withPE ratios are calculated, and the independent board based on the proportionof independent board does not have a moderating effecton the relationshipbetween CEO power and firm performance.